Beginning of Mesozoic marine overstep of the Mendips: The Rhaetian and its fauna at Hapsford Bridge, Vallis Vale, Somerset, UK. Issue 5 (October 2020) - Ronan, James; Duffin, Christopher J.; Hildebrandt, Claudia; Parker, Adam; Hutchinson, Deborah; Copp, Charles; Benton, Michael J.
Abstract: One of the most dramatic environmental changes in the Mesozoic history of Europe was the switch from terrestrial to marine deposition marked by the Rhaetian Transgression, 205 Ma. Beginning with this event, the Mendip Hills, composed primarily of uplifted and folded Lower Carboniferous limestones, were flooded in a stepwise manner from the Late Triassic to mid Cretaceous. The basal Rhaetian beds at the eastern end of the Mendips (Hapsford Bridge, Vallis Vale) lie directly on Carboniferous limestone, which was bored, indicating it functioned as a hardground. Bored pebbles were then eroded, transported, encrusted with bivalves, and deposited in marine muds in the lower parts of the Westbury Formation. At certain levels also, suspended mini-conglomerates within finer-grained sediments suggest continuing storm activity. The Hapsford Bridge Rhaetian bone bed includes microvertebrate remains of four species of sharks and two species of bony fishes, all of them typical of Rhaetian-aged bone beds. The invertebrate fauna is especially rich, including bivalves and echinoids, as well as trace fossils. Unusual elements are barnacles and a possible belemnite.